Strategies for Mitigating Dissolution of Solid Electrolyte Interphases in Sodium‐Ion Batteries. Issue 9 (8th January 2021) - Ma, Le Anh; Naylor, Andrew J.; Nyholm, Leif; Younesi, Reza
Abstract: The interfacial reactions in sodium‐ion batteries (SIBs) are not well understood yet. The formation of a stable solid electrolyte interphase (SEI) in SIBs is still challenging due to the higher solubility of the SEI components compared to lithium analogues. This study therefore aims to shed light on the dissolution of SEI influenced by the electrolyte chemistry. By conducting electrochemical tests with extended open circuit pauses, and using surface spectroscopy, we determine the extent of self‐discharge due to SEI dissolution. Instead of using a conventional separator, β‐alumina was used as sodium‐conductive membrane to avoid crosstalk between the working and sodium‐metal counter electrode. The relative capacity loss after a pause of 50 hours in the tested electrolyte systems ranges up to 30 %. The solubility of typical inorganic SEI species like NaF and Na2 CO3 was determined. The electrolytes were then saturated by those SEI species in order to oppose ageing due to the dissolution of the SEI. Abstract : The formation and dissolution of the solid electrolyte interphase (SEI) in sodium‐based systems is studied using a new cell setup. As a separator, β‐alumina is employed as a sodium‐conductive membrane to avoid crosstalk between the working electrode and sodium‐metal counter electrode. The SEI dissolution in different time domains is tested and mitigated with new additive strategies. A correlation between SEI dissolution and SEI chemistry is presented.